1986
DOI: 10.2320/matertrans1960.27.648
|View full text |Cite
|
Sign up to set email alerts
|

Solid Solution Hardening of Ni<SUB>3</SUB>Al with Ternary Additions

Abstract: An attempt is made to interpret the solid solution hardening of Ni3Al alloys in terms of the elastic interaction between the strain fields of a dislocation and a solute. Ternary additions are made to the L12 intermetallic compound with both B-subgroup and transition metal elements which substitute for Al-sites. Young's modulus of the ternary alloys is measured and the rate of change in elastic constant per one atomic per cent of solute (dE/dc) is determined. With the available data for the rate of solution har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 33 publications
(11 reference statements)
0
27
0
Order By: Relevance
“…In view of these previous works, the present results should be treated more carefully taking the effect of modulus change by ternary additions. An investigtion is now under way to provide comprehensive understanding on the degree of solid solution hardening not only by Bsubgroup elements but also by transition metal elements by the present authors (30).…”
Section: Solid Solution Hardeningmentioning
confidence: 94%
“…In view of these previous works, the present results should be treated more carefully taking the effect of modulus change by ternary additions. An investigtion is now under way to provide comprehensive understanding on the degree of solid solution hardening not only by Bsubgroup elements but also by transition metal elements by the present authors (30).…”
Section: Solid Solution Hardeningmentioning
confidence: 94%
“…The description of the solid solution strengthening contribution was based on the model proposed by Gypen and Deruyttere, [34] which assumes a superposition of strengthening of individual solutes based on their concentration in the matrix and precipitate phase, both of which were calculated using thermodynamic models in ThermoCalc. The empirical solid solution strengthening coefficients were derived from the work of Mishima et al [35] at 77 K and were further calibrated versus temperature using the trough model proposed by Roth et al [36] An average grain size of 15 lm was utilized in the calculations along with a grain size coefficient of 450 MPa lm À1/2 , as proposed by Parthasarathy et al [33] As the experimental yield strength data available was obtained on material aged using P-SHT1, the average secondary c¢ size obtained through image analysis for this condition (Figures 1(a) and (b)) was used as an input for the models, i.e., the secondary c¢ size was set to 152 nm for both alloys. However, as the elemental partitioning coefficients used in the calculations could not be experimentally obtained, ThermoCalc was used to estimate them and as a result, the volume fraction as predicted by ThermoCalc was also used in the calculations so as not change the underlying alloy composition.…”
Section: Discussionmentioning
confidence: 99%
“…In Ni 3 Al, solid solution hardening by several transition elements has been studied, and it has been found that the potency of the solid solution strengthening due to Nb atoms is much higher than that due to Ti atoms. 20) However, solid solution hardening behavior by transition metals in Ni 3 V has not been reported so far although Ni 3 V can be strengthened by refinement of variant structures in D0 22 phase. 21) These hardness levels may also be affected by the microstructure in another constituent, i.e., the channel region.…”
Section: The Effect Of Nb and Ti Addition On Hardnessmentioning
confidence: 99%